“AWAN DI ATAS TRUK” : CROSS-PROVINCE EXPEDITION DRIVER'S NARRATIVE - Martya Fani Muhardianti (Cinematology: Journal Anthology of Film and Television Studies, 2021)
The job of a truck driver sounds simple to the public's ears, but for truck drivers themselves, the profession they live has a different perspective in interpreting it. By crossing the province for three days and two nights the truck drivers only get wages with a small amount not commensurate with the risks and dangers they experience. The purpose of this study is to find out the perspective of truck drivers and how they react to it at work and injustice in the workplace. In fact, the job of truck drivers is not easy because in their work there are many obstacles that can sometimes endanger lives and problems that must be passed, especially from the trucks they use. Long journeys make their stamina must be maintained during the trip, from the agency itself which sometimes treats its employees as they please. With low wages, truck drivers still experience injustice, because if the truck used gets into trouble, be it engine failure, a single accident or a series of accidents, the cost of repairs will be borne by the truck driver himself, and sometimes agencies cut the salary of the truck driver without prior notification to the driver. truck. Qualitative method with descriptive analysis approach is used in this research. Through observation, in-depth interviews, and documentation studies, participatory techniques are also used to obtain various required data. This study found that the life of a truck driver is full of dynamic problems on the road, namely injustice in wages and no guarantee of job security. This research is data for the purposes of making a documentary film.